False positive angiographic aneurysm of the anterior segment of the M1 bifurcation of the middle cerebral artery: a case report - Xiao, Wen; Hou, Xiaolin; Li, Dingjun; Yang, Dongdong (Frontiers in Neurology, 2023)
Occlusion of an intracranial arterial branch, resulting in a false positive aneurysm on vascular imaging, is extremely rare, with only a few reports in the literature and mostly in the posterior circulation artery or the middle cerebral artery (MCA) bifurcation. We report a case of a 69 years-old woman with a subacute infarct lesion in the left frontal lobe, for whom both computed tomographic angiography (CTA) and digital subtraction angiography (DSA) of the cerebral vessels showed aneurysms in the anterior segment of the M1 bifurcation of the middle cerebral artery (MCA) and in the bifurcation of the MCA. The aneurysm in the MCA bifurcation was found during craniotomy, whereas the anterior segment of the M1 bifurcation had intact branch vessels with severe atherosclerosis and no aneurysm was present. The branch vessel of M1 was presumed to be atherosclerotic occlusion resulting in the distal vessels without contrast filling on CTA and DSA, and only the occluded stump at the beginning of the vessel was filled with contrast, showing an aneurysm-like morphology, which was very confusing. This case highlights to neurologists that the diagnosis of aneurysm by cerebrovascular CTA or DSA must be carefully differentiated to avoid misdiagnosis, especially if the unruptured aneurysm is in an uncommon location in combination with ischemic cerebrovascular disease.